Analysis of products, mechanisms of reaction, and some functional properties of soy protein hydrolysates - Molina Ortiz, Sara E. (2000)
Soybean protein isolates were hydrolyzed with papain, bromelain, cucurbita, hieronymin, and pomiferin. The highest hydrolysis rate for cucurbita and the lowest for papain was detected at 720 min. Gel filtration, reversed-phase liquid chromatography, and electrophoresis showed that the action of each protease was different. Pomiferin acted on the native structure of β-conglycinin and glycinin, generating a large number of small hydrolysis products with hydrophilic and hydrophobic characteristics. The hydrolysates obtained with cucurbita showed residual structures that were almost intact and very similar to the substrate and contained a low number of small peptides. The hydrolyzates obtained with papain, bromelain, and hieronymin had hydrolysis products with structures similar to the partially hydrolyzed native isolate. The molecular masses of these products were similar to or lower than the controls. Polypeptides of low molecular mass were also detected. The prevalence of one-by-one and zipper mechanisms was suggested for cucurbita and pomiferin, respectively. For the other proteases both mechanisms were likely to coexist. The solubility of hydrolysates and their ability to form and stabilize foams correlated well with the structural properties and with the suggested mechanisms of hydrolysis. The best properties were presented by the hydrolysates prepared with cucurbita. Foaming ability for pomiferin hydrolysates was as high as that for unhydrolyzed soy isolate, but the foams were extremely unstable.